Pengabdian untuk Negeri : Implementasi KKN melalui Kegiatan Kemerdekaan dan Keagamaan di Sialang Munggu - Putri, Sindy Eka; Ningsih, Fira Indarwati; Hermansyah, Fauzan; Anggraini, Reza Silvia; Raihana, Esti (Universitas Pahlawan Tuanku Tambusai, 2025)
The Community Service Program, known as KKN, is a way for students to give back to society through educational, social, and active participation activities. In Sialang Munggu Village, the KKN program was based on the theme